PENGARUH KUALITAS PELYANAN TERHADAP LOYALITAS DAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DALAM MENGGUNAKAN JASA TRANSPORTASI BUS “ PO.TITIAN MAS “ (Studi kasus Pada Mahasiswa Bima,Dompu Universitas Islam Malang) - Kurniati Kurniati; Agus Widarko; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this study was to determine the quality of service directly affect Loyalty in using bus transportation services "PO.TITIAN MAS". To find out the quality of service has a direct effect on Consumer Satisfaction in using bus transportation services "PO TITIAN MAS". To know customer satisfaction has a direct effect on loyalty in using bus transportation services "PO.TITIAN MAS". To find out the quality of service indirect effect on loyalty through customer satisfaction as an intervening variable in using bus transportation services "PO. TITIAN MAS ".This type of research uses explanatory research, this research was conducted on customers of Bus Po.Titian Mas. The population in this study were students of Bima, Dompu who studied at Islamic University of Malang in October to November 2019 with 818 customers. this study amounted to 89 respondents with purposive sampling technique.The results of this study indicate that Service Quality directly has a positive and significant effect on Consumer Satisfaction in using the transportation services of Bus Po.Titian Mas. Service Quality directly has a positive and significant effect on Loyalty in using the services of Po.Titian Mas Bus transportation. Consumer Satisfaction directly positive and significant effect on loyalty in using Bus Po.Titian Mas transportation services. Service quality indirectly affects Loyalty with customer satisfaction as an intervening variable in using Po.Titian Mas Bus transportation services. Keywords: Service Quality, Loyalty, Consumer Satisfaction